Development and usefulness of the new endoscopic classification: DICA - Cambiè, Ginevra; Violi, Alessandra; Miraglia, Chiara; Barchi, Alberto; Nouvenne, Antonio; Capasso, Mario; Leandro, Gioacchino; Meschi, Tiziana; de' Angelis, Gian Luigi; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2018)
Colonic Diverticulosis is one of the most common anatomical findings during colonoscopy. This condition has 60% incidence in the population over 60 years old. About 20% of patients will develop Diverticular Disease, and 5% of them will evolve into Diverticulitis. Until the last years there weren’t any approaches for the endoscopic classification of this pathology. In 2013, in Florence, the first endoscopic classification was developed: DICA (Diverticular Inflammation and Complication Assessment). The aim of this article is to focus on the process of the development and the validation of the classification by the pool of gastroenterology experts, and, as well, its usefulness during the clinical practice.